Determinación de cocaina, marihuana, éxtasis, heroína anfetaminas y benzodiacepinas en orina por el método Multidrogas en los estudiantes del Bachillerato del Colegio Hernán Gallardo Moscoso de la ciudad de Loja. - Espejo Medina, Alicia Lorena (2013)
Given the drug problems of global, national and local development was proposed this research entitled "DETERMINATION OF COCAINE, MARIJUANA, ECSTASY, HEROIN, Amphetamines and BENZODIAZEPINES IN URINE Multidrug BY THE METHOD OF HIGH SCHOOL STUDENTS COLLEGE BACHELOR HERNÁN GALLARDO MOSCOSO OF THE CITY OF Loja ", with the aim of analyzing the presence of drugs in adolescents, and in this way establish what is the average age of consumption and what is the most affected gender in high school students Hernán Gallardo Moscoso College of the city of Loja. For these reasons and in view of the above there have been no studies focused on this population, it was important to the development of this research work in which we applied a descriptive study and cross-sectional, which sampled 62 people the same as met the inclusion criteria and were analyzed by immunoassay techniques. Thus leading to the conclusion that there were 3 positive cases, all male and aged between 16 and 19 years. Also it was established that both family factors such as social are leading to most of the young people with drug and curiosity by them to experience new emotions. Given that adolescents are big risk takers. KEYWORDS: Drugs, Teen, Multidrogas method.